Economic and Ecological Evaluation of Land Use Change (Evidence from Karelia) - Strokov, Anton Sergeevich; Yakubovich, Ekaterina Nikolaevna; Krasilnikov, Pavel Vladimirovich (Economy of Regions, 2017)
Land use change and a shift in economic activity often bring to unpredictable consequences for local ecosystems. There is a necessity of making preliminary evaluation and analysis of comparing the different types of economic and ecological transformation, including cost and benefit analysis, not only for business and local population, but for the whole environment. We give an example of a particular animal husbandry farm in Karelia and show how potential change in economic specialization can be effective on a 10 years horizon. Among other land use types, we chose peat mining and wetland conservation. Each type of activities was complexly evaluated with different types of costs and benefits. In the paper, we use a method of land use change evaluation including the value of ecosystem services. The monetary values of ecosystem services are given with the respect to foreign analogues and taking into account local realities and prices. Our results have shown that the most beneficial for the society and the environment is wetland conservation, due to their berries picking service, which are highly appreciated on the market, and due to low costs for the third parties, since wetlands contain regulative and refinery services for local ecosystems. As a contrary peat mining is a profitable business, but pollutes the environment because of carbon emissions into the atmosphere. The current specialization for animal husbandry is neither an optimal solution because of low profitability of the chosen farm. The results of the research can be used for optimization in regional politics in the sphere of agriculture and environment economics in order to protect the ecological balance between human activities and nature.